Association of serum omentin-1 levels with coronary artery disease - Zhong Xia; Zhang Hai-yang; Tan Hui; Zhou Yi; Liu Fu-li; Chen Fu-qin; Shang De-ya (Acta Pharmacologica Sinica, 2016)
Aim: Omentin-1, a novel adipokine expressed in visceral adipose tissue, is negatively correlated with insulin resistance and obesity. Decreased omentin-1 expression has been found in many chronic inflammatory diseases. However, the role of omentin-1 in coronary artery disease (CAD) has not been elucidated. The aim of the present study was to determine whether serum concentration of omentin-1 was independently associated with CAD. Methods: One hundred and fifty five patients with CAD were divided into two groups: acute coronary syndrome (ACS) and stable angina pectoris (SAP). A total of 52 healthy participants served as controls. Serum concentrations of omentin-1 and interleukin-6 (IL-6) were measured using ELISA. The association of omentin-1 with CAD and cardiovascular disease risk factors was evaluated. Results: Serum omentin-1 levels were lower in patients with ACS or SAP compared with controls (ACS, 113.08±61.43 ng/mL; SAP, 155.41±66.89 ng/mL; control, 254.00±72.9 ng/mL; P